Analisis Elemen Visual Postingan Konten Infografis Edukasi pada Feed Akun Instagram @ditjentataruang Edisi Januari 2025 - Fariq Hasril Adiwardana; David Rizar Nugroho (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Social media, particularly Instagram, has become a strategic medium for government institutions to disseminate policy-related information to the public. This study aims to analyze how visual elements are applied in educational infographic content on the Instagram account @ditjentataruang, specifically in the January 2025 edition, using the theory of visual hierarchy. A qualitative descriptive method was employed, with data collected through visual observation, in-depth interviews with the content designer, and documentation. Four infographic posts were selected as the subjects of analysis, each examined based on elements of color, typography, layout and composition, and visual imagery. The results indicate that the use of visual elements in the infographics is not arbitrary, but designed with a clear visual communication strategy. Green is consistently used as the institution's visual identity and a marker of visual stability. Typography is structured hierarchically to guide the reading flow, and layouts are designed using Z or C patterns to direct audience attention. In addition, visualizations such as icons and photographs are used to reinforce messages and create concrete context. These findings are strengthened through data triangulation involving observation, interviews, and supporting theories, confirming that the infographic content by the Directorate General of Spatial Planning applies the principles of visual hierarchy consciously and strategically in delivering public information.